Provenance Variations in Seed Characteristics and Germination Behaviour of Terminalia arjuna and Terminalia tomentosa - Hembrom, I., Gargi; Kumar, R.; Singh, M. K.; Vijayaprakash, N. B. (Indian Forester, 2011)
Studies for seed morphology, seedling growth and biomass attributes were made in 25 provenances of Terminalia arjuna (11) and T. tomentosa (14). A wide variation was recorded for 13 seed and seedling traits in both the species. Single seed weight ranged between 1.15 to 4.52 g in T. arjuna and 0.87 to 2.76 g in T. tomentosa. Germination per cent was maximum (83.33) in T. arjuna seeds from Chakradharpur (Jharkhand). Production of fresh biomass was maximum (2.03 g) in T. tomentosa seedlings from Kharsawan (Jharkhand). Root shoot ratio an important parameter in initial establishment of seed ling was also highest (3.08:1) in seedlings of T. tomentosa from Ranka (Jharkhand).Vigour index ranged between 669.80% (T. arjuna) to 580.80 % in T. tomentosa. A positive and significant correlation was found between emergence index and germination per cent, germination speed, root length and vigour index. Based on the vigour index, root/shoot ratio plus trees of T. arjuna from Chakradharpur and Garwha and of T. tomentosa from Baharagoda have been identified for multiplication.